2020
DOI: 10.3390/en13071744
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Normal Impinging Water Jet at Different Impinging Height, Based on Wray–Agarwal Turbulence Model

Abstract: As a kind of water jet technology with strong impinging force and simple structure, the submerged impinging water jet can produce strong scouring action on subaqueous sediments. In order to investigate the flow field characteristics and impinging pressure of submerged impinging water jets at different impinging heights, the Wray-Agarwal (W-A) turbulence model is used for calculation. The velocity distribution and flow field structure at different impinging heights (1 ≤ H/D ≤ 8), and the impinging pressure dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…In this paper, the maximum y+ was less than 1 to ensure that the near wall treatment for the W-A model was accurate. Wang et al [20] and Han et al [27] carried out a comparison between numerical simulations and experimented on various turbulence models, including the W-A model. The results showed that the W-A model simulates the separation characteristics of the boundary layer more accurately and has good applicability in a numerical simulation of a submerged jet.…”
Section: Geometric Model and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the maximum y+ was less than 1 to ensure that the near wall treatment for the W-A model was accurate. Wang et al [20] and Han et al [27] carried out a comparison between numerical simulations and experimented on various turbulence models, including the W-A model. The results showed that the W-A model simulates the separation characteristics of the boundary layer more accurately and has good applicability in a numerical simulation of a submerged jet.…”
Section: Geometric Model and Boundary Conditionsmentioning
confidence: 99%
“…The results showed that the improved SPH method can accurately simulate the shape and pressure distribution of an impinging jet. Based on the W-A turbulence model, Wang et al [20] used CFD technology to study the flow characteristics of a submerged impinging water jet at different impact heights. The results show that there is a negative correlation between impact pressure, impact pressure coefficient and impact height.…”
Section: Introductionmentioning
confidence: 99%
“…Pump performance has an important influence on realizing an efficient pump operation. Given the extensive application of pumps in different fields, including hydraulic engineering, chemical industry, manufacturing, and environmental protection [1,2], studies on the performance of centrifugal [3,4], axial flow [5], sewage [6], submersible well [7], fully tubular [8], and multistage [9,10] pumps have been conducted using various advanced methods and technologies, such as numerical simulation [11], experimental analysis, and intelligent fault diagnosis [12,13]. Focus should also be placed on the operating process of pump units because, sometimes, actual working conditions may exceed the designed range, which means that pump performance is effectively influenced by external conditions with frequent change.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of fluid machinery, some scholars use pure simulation methods to study its performance index (Shi et al, 2020a;Shi et al, 2020b;Wang et al, 2020a;Wang et al, 2020b), some scholars adopt the method of combining simulation methods with experiments (Wang et al, 2018;Shi et al, 2020), and this study adopts the method of direct experiment.…”
Section: Introductionmentioning
confidence: 99%